Effect of High Doses Gamma Irradiation on Texturing of Bi2Sr2CaCu2O8 (Bi-2212) Superconductor - Hamid N.A.; Mohiju Z.A.; Senduradesigen P. (IOP Publishing Ltd, 2023)
Bismuth compounds; Bismuth metallography; Calcium compounds; Copper compounds; Irradiation; Strontium compounds; Superconducting materials; Sustainable development; Textures; X ray diffraction; Gamma irradiation; Grain microstructure; Irradiated samples; Powder X ray diffraction; Radiation environments; Scanning electrons; Texture and microstructures; Texture coefficient; Gamma rays